The Alleviation of LPS-Induced Murine Acute Lung Injury by GSH-Mediated PEGylated Artesunate Prodrugs - Hao, Dan-Li; Wang, Ya-Jie; Yang, Jia-Ying; Xie, Ran; Jia, Ling-Yu; Cheng, Jin-Tang; Ma, Hai; Tian, Ji-Xiang; Guo, Shan-Shan; Liu, Ting; Sui, Feng; Zhao, Yu; et al. (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) or its aggravated stage acute respiratory distress syndrome (ARDS) is a common severe clinical syndrome in intensive care unit, may lead to a life-threatening form of respiratory failure, resulting in high mortality up to 30–40% in most studies. Nanotechnology-mediated anti-inflammatory therapy is an emerging novel strategy for the treatment of ALI, has been demonstrated with unique advantages in solving the dilemma of ALI drug therapy. Artesunate (ART), a derivative of artemisinin, has been reported to have anti-inflammatory effects. Therefore, in the present study, we designed and synthesized PEGylated ART prodrugs and assessed whether ART prodrugs could attenuate lipopolysaccharide (LPS) induced ALI in vitro and in vivo. All treatment groups were conditioned with ART prodrugs 1 h before challenge with LPS. Significant increased inflammatory cytokines production and decreased GSH levels were observed in the LPS stimulated mouse macrophage cell line RAW264.7. Lung histopathological changes, lung W/D ratio, MPO activity and total neutrophil counts were increased in the LPS-induced murine model of ALI via nasal administration. However, these results can be reversed to some extent by treatment of ART prodrugs. The effectiveness of PEG2k-SS-ART in inhibition of ALI induced by LPS was confirmed. In conclusion, our results demonstrated that the ART prodrugs could attenuate LPS-induced ALI effectively, and PEG2k-SS-ART may serve as a novel strategy for treatment of inflammation induced lung injury.